COGNITIVE DEFICITS AND FUNCTIONAL OUTCOMES IN MAJOR DEPRESSIVE DISORDER: DETERMINANTS, SUBSTRATES, AND TREATMENT INTERVENTIONS. Issue 6 (6th March 2013) - McIntyre, Roger S.; Cha, Danielle S.; Soczynska, Joanna K.; Woldeyohannes, Hanna O.; Gallaugher, Laura Ashley; Kudlow, Paul; Alsuwaidan, Mohammad; Baskaran, Anusha
<x xml:space="preserve">Abstract</x> Background Few reports have aimed to describe the mediational effect of cognitive deficits on functional outcomes in major depressive disorder (MDD), and relatively few interventions are demonstrated to mitigate cognitive deficits in MDD. Methods Studies enrolling subjects between the ages of 18–65 were selected for review. Bibliographies from identified articles were reviewed to identify additional original reports aligned with our objectives. Results Cognitive deficits in MDD are consistent, replicable, nonspecific, and clinically significant. The aggregated estimated effect size of cognitive deficits in MDD is small to medium. Pronounced deficits in executive function (≥1 SD below the normative mean) are evident in ∼20–30% of individuals with MDD). Other replicated abnormalities are in the domains of working memory, attention, and psychomotor processing speed. Mediational studies indicate that cognitive deficits may account for the largest percentage of variance with respect to the link between psychosocial dysfunction (notably workforce performance) and MDD. No conventional antidepressant has been sufficiently studied and/or demonstrated robust procognitive effects in MDD. Conclusions Cognitive deficits in MDD are a principal mediator of psychosocial impairment, notably workforce performance. The hazards posed by cognitive deficits in MDD underscore the need to identify a consensus‐based neurocognitive battery for research and clinical purposes. Interventions (pharmacological, behavioral, neuromodulatory) that engage multiple physiological systems implicated in cognitive deficits hold promise to reduce, reverse, and prevent cognitive deficits.